2002
DOI: 10.1021/ja0200847
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Lanthanide Complexes of a Bis-bipyridine-phosphine-oxide Ligand as Tools for Anion Detection

Abstract: The Gd(3+), Tb(3+), and Eu(3+) complexes of a bis-bipyridine-phenylphosphine oxide ligand PhP(O)(bipy)(2) 1 (bipy for 6-methylene-6'-methyl-2,2'-bipyridine) have been synthesized. In acetonitrile solutions at room temperature, the Tb(3+) and Eu(3+) complexes show a metal-centered luminescence, indicative of an efficient energy transfer from the two bipy subunits to the Ln center. The photophysical properties drastically depend on the nature of the anions present in solution. In particular, addition of 2 equiv … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 195 publications
(108 citation statements)
references
References 28 publications
(38 reference statements)
5
103
0
Order By: Relevance
“…Charbonniere et al 148 observed the increase of the Eu complex luminescence lifetime (combining a hard donor with two soft pyridine donors) upon the addition of ATP, whereas ADP and AMP did not induce significant changes. Ln ions in liquid chromatography 149 can also serve the purpose of detection of single stranded nucleic acids, 150 hormones, 151 amino compounds 152 and labeled thiols.…”
Section: Ion Ph and Hydrocarbon Sensorsmentioning
confidence: 99%
“…Charbonniere et al 148 observed the increase of the Eu complex luminescence lifetime (combining a hard donor with two soft pyridine donors) upon the addition of ATP, whereas ADP and AMP did not induce significant changes. Ln ions in liquid chromatography 149 can also serve the purpose of detection of single stranded nucleic acids, 150 hormones, 151 amino compounds 152 and labeled thiols.…”
Section: Ion Ph and Hydrocarbon Sensorsmentioning
confidence: 99%
“…Spectrophotometric and fluorimetric titrations and data analysis were carried out as elsewhere described [13].…”
Section: Photophysical Measurementsmentioning
confidence: 99%
“…[1,2] Lanthanide complexes are increasingly used for sensor development [3] and as luminescent probes in time-resolved high-throughput assays and fluorescence imaging because of their ability to discriminate between background fluorescence and the target signal. [4][5][6][7][8] Numerous studies have been directed to design efficient luminescence probes containing the long-lived visible emitters Eu iii and Tb iii [9][10][11][12][13][14] and more recently near-infrared (NIR) emitters (Pr iii , Er iii , Yb iii , Nd iii ). [15][16][17][18] As the Laporte-forbidden 4f-4f transition prevents direct excitation of lanthanide luminescence, lanthanide ions require sensitization by suitable organic chromophores.…”
mentioning
confidence: 99%